Fast self-healing superhydrophobic sponge with all-weather heating and anti-fouling properties. (March 2022) - Li, Ruiqi; Yang, Lixue; Zhou, Changqing; Zhang, Guoli; Tian, Jiaxiang; Wu, Wencong
Abstract: The loss of superhydrophobicity due to mechanochemical damage is critical for superhydrophobic surfaces, and rapid self-healing is significant in maintaining surface durability. Herein, a novel, fast, self-healing superhydrophobic sponge capable of all-weather heating was polymerized in an eco-friendly aqueous system and dip-coated using fluorine-free and non-toxic reagents. Benefiting from the photothermal and Joule-heating performance of polyaniline (PANI) and multiwalled carbon nanotubes (MWCNTs), all-weather heating could be achieved. The equilibrium surface temperature (EST) of the as-prepared sponge could rapidly reach 105°C under irradiation of 1.0 kW/m 2 for 20 s, and the EST exceeded 120°C with supplementary 18 V treatment. Impressively, after O2 plasma etching for 1 min or after being immersed in hydrogen peroxide (H2 O2 ) solution for 24 h, the water contact angle (WCA) of self-healing superhydrophobic polyurethane (PU) sponge (SHSPS) can be restored to 155°C under simulated sunlight for 2 min because of the rapid migration of low surface energy polydimethylsiloxane (PDMS) chains, which is the fastest recovery achieved to the best of our knowledge. In addition, the modified sponge exhibited a significant antifouling capability for particulate contaminants and organic pollutants, extending service life. Our preliminary results demonstrated that the modified sponge prepared in the current work is fully qualified in multiple applications, including oil-water separation, viscous oil treatment, seawater evaporation and desalination, de-icing, and anti-icing. Graphical abstract: Image 1 Highlights: Non-fluorinated antifouling self-healing superhydrophobic sponges were prepared. The sponges exhibit solar-heating and Joule-heating performance. The sponge can self-heal severe mechanochemical damage within 2 min. The sponges are fabricated by an eco-friendly process. The sponges are competitive in multiple applications.